1인 가구 성인의 가정간편식 이용과 식습관 실태 - 최미경(Mi-Kyeong Choi); 박은선(Eun-Sun Park); 김미현(Mi-Hyun Kim) (Korean journal of community nutrition, 2019)
Objectives: The rise of one-person households may have consequences for food consumption patterns, and eating habits. This study investigated the home meal replacement (HMR) use and eating habits among adults in their 20s-30s living in one-person households. Methods: A total of 247 adults aged 26-39 years participated in this study. The subjects were divided into three group according to the household type; one-person households (n=80), two-person households (n=49), and multi-family (three and more members) households (n=118). Their use of HMRs (classified as ready-to-eat, ready-to-cook, and fresh convenience foods) and their eating habits were all compared. Results: The mean age of the subjects was 30.5 years, 47.8% were male, and there was no significant difference in age, gender, occupation, and monthly income according to the type of household. The intake frequency of total HMR and ready-to-eat foods was significantly higher in one-person households among the three groups. People in one-person households consumed more HMRs alone, and spent more money to buy HMRs. Undesirable dietary habit scores like unbalanced eating (p<0.05) and eating salty foods (p<0.05) were significantly higher in the one-person households. Among the total subjects, the unbalanced eating scores showed a significant positive correlation with the intake frequency of ready-to-eat foods, while the unbalanced eating scores showed negative correlation with the preference of fresh convenience foods. The scores for eating salty foods showed a significant positive correlation with the intake frequency and preference of ready-to-eat foods and ready-to-cook foods, while there was negative correlation with the intake frequency and preference of fresh convenience foods. Conclusions: Adults in their 20s-30s in one-person households consumed more ready-to-eat foods than those in multi-family households. In addition, people with one-person households had more unbalanced diets and ate more salty foods, and these undesirable eating habits showed a significant positive correlation with the use of ready-to-eat or ready-to-cook foods. These results should be addressed for producing healthier ready-to-eat/ready-to-cook foods and implementing nutrition education for making healthy food choices of one-person households, which are steadily increasing.